Community Cultural Wealth: The Care and Resilience of Mothers in Poverty - Colleen Janey:::::: (2024)
After inductively coding 52 interview transcripts using Atlas.ti as part of my Independent Study course in the Fall of 2023, I delved into the literature to help deepen my understanding of the themes that emerged in the lived experiences of mothers navigating through poverty. The CSUSM Library Award for Undergraduate Research, Scholarship and Creative Activity recognizes undergraduate students who demonstrate sophistication and originality in research projects and creative works, and reflection upon the research/creation process. Up to six prizes will be awarded in three categories: Creative Works, Empirical Research and Interpretive Analysis. Winners receive a cash prize and public recognition of their excellent work. Submissions by individuals or groups will be considered in the following three categories: Creative Works, including, but not limited to, an art installation, software program, musical composition, film or video, special project, etc. Empirical Research, including, but not limited to, research conducted with qualitative or quantitative methodologies using the (social-) scientific method. Interpretive Analysis, including, but not limited to, analysis which aims to capture hidden meaning and ambiguity of a cultural artifact.